2008
DOI: 10.1007/s10562-008-9488-3
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Electrocatalytic Fischer–Tropsch Synthesis from Carbon Dioxide Over Copper-based Electrodes

Abstract: We report on the discovery that paraffins and olefins up to C 6 hydrocarbons can be obtained in CO 2 electroreduction at room temperature and atmospheric pressure by application of a commercially available Cu-electrode (Eurofysica), provided pretreatment by electropolishing is avoided. The product distribution follows the Schultz-Flory distribution and, depending on the applied potential, the chain growth probability (α) ranges from 0.23 to 0.31, values lower than those obtained in Fischer-Tropsch synthesis ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 25 publications
4
82
2
4
Order By: Relevance
“…Recent results even show that for specific Cu electrodes Fischer-Tropsch distributions are encountered, see Fig. 4 [19]. The Faradaic efficiency is low, mainly because of the competing dissociation of water.…”
Section: Reaction Pathwaysmentioning
confidence: 96%
See 2 more Smart Citations
“…Recent results even show that for specific Cu electrodes Fischer-Tropsch distributions are encountered, see Fig. 4 [19]. The Faradaic efficiency is low, mainly because of the competing dissociation of water.…”
Section: Reaction Pathwaysmentioning
confidence: 96%
“…Two other major routes suggest themselves, for storing the collected photonic energy in the form of chemicals: -H 2 production by water splitting [11][12][13][14][15][16] -CO 2 reduction, combined with water oxidation (to O 2 ), yielding liquids such as alcohols or even hydrocarbons. This process is commonly referred to as artificial photosynthesis [17][18][19][20][21][22][23].…”
Section: Minerals (Including P and N In Suitable Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some recent papers have identified potentially promising pathways (Qiao et al, 2014;Studt et al, 2014;Albo et al, 2015). Centi et al (2007) and Shibata et al (2008) have published tantalizing studies indicating that it is possible to produce C 4+ products electrochemically. Centi et al in particular even point to aromatics as a specific class of products produced.…”
Section: Methanolmentioning
confidence: 99%
“… EC CO 2 RR can only make C 1 -C 3 products with appreciable Faradaic efficiency (Section 2 of the Supplementary Information contains a list of all possible products), although a few studies have indicated the possible production of products with four or more carbon atoms (e.g., Centi et al, 2007;Shibata et al, 2008).  Certain C 1 products, such as CO and formate, can be made with high selectivity, but selectivity to C 2 products such as C 2 H 4 and/or ethanol remains poor.…”
mentioning
confidence: 99%